UPLC-ESI-QTOF-MS Profiling of Phenolic Compounds from Eriocephalus africanus: In Vitro Antioxidant, Antidiabetic, and Anti-Inflammatory Potentials - Kunle Okaiyeto; Nasifu Kerebba; Oluwafemi O. Oguntibeju (Molecules, 2022)
The present study investigated phenolic compounds, antioxidant, antidiabetic, and the anti-inflammatory potentials of methanolic and chloroform extracts of Eriocephalus africanus. The methanolic extract included, polyphenols (112 ± 2.81 mg gallic acid equivalent (GAE)/g), flavonols (76.12 ± 7.95 mg quercetin equivalents (QE)/g); antioxidant capacity (Ferric Reducing Antioxidant Power (FRAP) (752.64 ± 89.0 μmol of ascorbic acid equivalents (AAE) per g dry weight (µmol AAE/g), 2,2-dyphenyl-1-picrylhydrazyl (DPPH) (812.18 ± 51.12 Trolox equivalents per gram of dry mass of plant extracts (μmol TE/g), TEAC (631.63 ± 17.42 µmol TE/g)), while the chloroform extract included polyphenols (39.93 ± 1.36 mg GAE/g), flavonols (44.81 ± 3.74 mg QE/g); antioxidant capacity, DPPH (58.70 ± 5.18 µmol TE/g), TEAC (118.63 ± 3.74 µmol TE/g) and FRAP (107.10 ± 2.41 µmol AAE/g). The phytochemicals profiling performed by UPLC-ESI-QTOF-MS revealed some important polyphenols, predominantly flavonoids, that could be responsible for the antioxidant capacity and biological effects. Both extracts demonstrated a dose-dependent manner of the alpha-glucosidase inhibition with an IC50 between 125 and 250 μg/mL for methanolic extract, while the chloroform extract was at 250 μg/mL. In the L6 myoblasts and C3A hepatocytes, the methanolic extract slightly increased the utilization of glucose, and both extracts exhibited a dose-dependent increase in the glucose uptake in both cell types without significantly increasing the cytotoxicity. Furthermore, both extracts exhibited an anti-inflammatory potential and the findings from the present study could serve as a baseline for further research in the development of pharmaceutical agents.